If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -4y = -9 Solving 11 + -4y = -9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -4y = -9 + -11 Combine like terms: 11 + -11 = 0 0 + -4y = -9 + -11 -4y = -9 + -11 Combine like terms: -9 + -11 = -20 -4y = -20 Divide each side by '-4'. y = 5 Simplifying y = 5
| y+5=2y-3 | | 3+3x=x+13 | | 2(2d+5)=3(8-d) | | n^2-18n+81=40 | | X-2+4x=38 | | Cx+hy= | | (A-9)(2a-1)=0 | | 25600p=(p+12)(-p+20) | | -3b+-b= | | bx+hy=kforx | | 9p+2=4p-11 | | c=1/2mr | | -10x+50=400 | | 42/b=14 | | 27+3y-11=15y-12-5y | | -4.9x-6=-4.1x+2 | | 3(-2)-y=2 | | 100+10= | | 5n-2=-32 | | 7(k+8)+8=2 | | 2(2z-2)-2(3-4z)=4 | | log(6)36=4x+4 | | 20/14=t/35 | | a^7b^6-a^5b^4+a^4b^9-a^4b^4= | | 7v-9=10+6(v+7) | | 3z=2.9+0.4 | | -15x-3y=5 | | 3-6=11+2x | | 10x-5+8x=5(6x-2)+2 | | 7y-21x=7 | | -4=w-3/4 | | 0.6m=-18 |